Heat transfer of nanostructure coating on commercially micro-enhanced refrigerant tubes under pool boiling and falling film boiling conditions - Bock, Bradley D. (University of Pretoria, 2023)
Dissertation (MEng (Mechanical))--University of Pretoria, 2023.